Diagnosis and Management of Bacterial Vaginosis in Pregnant Women - Rizky Aprilia Wikayanti; Bagus Pratama; Rodiani (MAJORITY, 2022)
Bacterial vaginosis is a disease that is a public health problem, especially in women, both non-pregnant and pregnant women. Bacterial vaginosis is caused by an excess and overgrowth of anaerobic bacteria such as Gardnerella vaginalis, Ureaplasma urealyticum, Mycoplasma hominis, Mobiluncus sp., Prevotella sp., and other anaerobic bacteria. Bacterial vaginosis is characterized by the presence of an itchy greyish white discharge with a fishy odor, an increase in the pH of the vaginal fluid and is found clue cells on Whiff's test using KOH10%. Management of bacterial vaginosis is in the form of antibiotics with the drug of choice being metronidazole 500 mg orally twice a day for 7 days. In pregnant women, bacterial vaginosis has been reported to increase the incidence of abortion, premature rupture of membranes, preterm labour, low birth weight, and intrauterine infection. Therefore, early diagnosis and appropriate management of bacterial vaginosis can reduce maternal and infant morbidity and mortality.